Cenozoic climate changes: A review based on time series analysis of marine benthic δ18O records. (11th August 2014) - Mudelsee, Manfred; Bickert, Torsten; Lear, Caroline H.; Lohmann, Gerrit
Abstract The climate during the Cenozoic era changed in several steps from ice‐free poles and warm conditions to ice‐covered poles and cold conditions. Since the 1950s, a body of information on ice volume and temperature changes has been built up predominantly on the basis of measurements of the oxygen isotopic composition of shells of benthic foraminifera collected from marine sediment cores. The statistical methodology of time series analysis has also evolved, allowing more information to be extracted from these records. Here we provide a comprehensive view of Cenozoic climate evolution by means of a coherent and systematic application of time series analytical tools to each record from a compilation spanning the interval from 4 to 61 Myr ago. We quantitatively describe several prominent features of the oxygen isotope record, taking into account the various sources of uncertainty (including measurement, proxy noise, and dating errors). The estimated transition times and amplitudes allow us to assess causal climatological‐tectonic influences on the following known features of the Cenozoic oxygen isotopic record: Paleocene‐Eocene Thermal Maximum, Eocene‐Oligocene Transition, Oligocene‐Miocene Boundary, and the Middle Miocene Climate Optimum. We further describe and causally interpret the following features: Paleocene‐Eocene warming trend, the two‐step, long‐term Eocene cooling, and the changes within the most recent interval (Miocene‐Pliocene). We review the scope and methods of constructing Cenozoic stacks of benthic oxygen isotope records and present two new latitudinal stacks, which capture besides global ice volume also bottom water temperatures at low (less than 30°) and high latitudes. This review concludes with an identification of future directions for data collection, statistical method development, and climate modeling.